Hirschsprung′s disease: Management problem in a developing country - Bandré E; Kaboré R.A.F; Ouedraogo I; Soré O; Tapsoba T; Bambara C; Wandaogo A (Wolters Kluwer Medknow Publications, 2010)
Background: The management of Hirschsprung′s disease remains a problem in developing countries. Our aim is to identify the main epidemiological, clinical, and therapeutic characteristics of Hirschsprung′s disease at the University Child Hospital Charles De Gaulle of Ouagadougou (CHUP-CDG). Patients and Method: It is a retrospective study carried out in the period from January 2001 to December 2007 in the Surgery Unit at CHUP-CDG, which is a reference centre for Paediatric Surgery in Burkina Faso. Results: There were 52 patients (M: F=3.3:1). The annual incidence was seven cases. Age at presentation and diagnosis ranged from two days 10 years (median 20 months). Twenty five patients were from poor socio-economic conditions. Presentations were mainly intestinal obstruction, chronic constipation and enterocolitis. There were two cases of associated trisomy 21. Average age at operative intervention was 3.17 months. The rectosigmoidal form was the most frequently encountered. Over two-thirds (67.31%), with no complications at presentation, had benefited from nursing before their final treatment. A temporary colostomy was requested in case of complication. Swenson′s technique was practiced for all the patients who underwent surgery operation. The assessment of functional results in eight patients after an average decrease of 3.5 years gave excellent results. Post-surgery complications were mainly enterocolitis in 12% of patients. Mortality rate was 16%. Conclusion: Management of Hirschsprung′s disease is a problem in Burkina Faso. It is characterised by its late presentation and difficult diagnosis due to inaccessibility and the non-availability of some investigation services (barium enema, histochemistry, and histology), resulting in high morbidity and mortality rates. Effective technical capacities, adequate staff training, and public education will be necessary to improve care quality.